Curbing of Illegal Construction of Facilities in Sustainable Cities and Communities: Velimir Rakočević, Aleksandra Rakočević (The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems, 2024)
The subject of research is environmental endangerment by unsustainable space management. The aim is to point out the harmful consequences of the irrational consumption of natural resources due to the overdimensioning of construction areas. The research results show that Montenegro has been unsuccessful in fighting the problem of illegal construction and legalisation of these buildings for over thirty years. Official data from state institutions report approximately 100,000 illicit buildings in Montenegro. To protect the environment, the state has prescribed three new criminal offences, such as construction of an object without registration and construction documentation, construction of a complex engineering object without a construction permit and illegal connection to the infrastructure. The Law on the Regulation of Informal Buildings and the Criminal Code are not implemented in a legally valid manner, and the penal policy does not act as a disincentive while the level of devastation of space increases.